2010
DOI: 10.1007/s10661-010-1456-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of trace elements in the tissues of smooth hound Mustelus mustelus (Linnaeus, 1758) from the southern–eastern waters of Mediterranean Sea (Italy)

Abstract: Trace element concentrations (Hg, Cd, Pb, Cr, Ni, Cu, Zn) were determined in the muscle, gonads, skin, and brain of smooth hound Mustelus mustelus in order to define the metal distribution patterns. The data indicated that metal accumulation depended on the tissues probably as a consequence of metabolic needs, physiochemical properties, and detoxification processes specific for each element. Metal concentrations were higher in gonads (Hg 0.10-0.70 μg g(-1); Cd 0.02-0.10 μg g(-1); Pb 0.08-0.39 μg g(-1); Cr 0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…This finding is well illustrated by the strong associations between body length and muscle Hg concentrations that have been observed for several shark species (Turoczy et al 2000;Gelsleichter and Walker 2010;Storelli et al 2011;Hurtado-Banda et al 2012;Maz-Courrau et al 2012;Delshad et al 2012). In the current study, although all scalloped hammerhead sharks were juvenile with relatively low variation in body size, significant correlations were found between total length and weight and Hg concentration in muscle and liver, but it was found that Hg in muscle increased and Hg in liver decreased as total length and weight incremented.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This finding is well illustrated by the strong associations between body length and muscle Hg concentrations that have been observed for several shark species (Turoczy et al 2000;Gelsleichter and Walker 2010;Storelli et al 2011;Hurtado-Banda et al 2012;Maz-Courrau et al 2012;Delshad et al 2012). In the current study, although all scalloped hammerhead sharks were juvenile with relatively low variation in body size, significant correlations were found between total length and weight and Hg concentration in muscle and liver, but it was found that Hg in muscle increased and Hg in liver decreased as total length and weight incremented.…”
Section: Discussionmentioning
confidence: 61%
“…One of the reasons why sharks tend to accumulate high concentrations of toxic metals, such as Hg, in their flesh is because they are long-lived species (Storelli et al 2011). This finding is well illustrated by the strong associations between body length and muscle Hg concentrations that have been observed for several shark species (Turoczy et al 2000;Gelsleichter and Walker 2010;Storelli et al 2011;Hurtado-Banda et al 2012;Maz-Courrau et al 2012;Delshad et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Available literature have generally reported low concentrations of Cu in various species of sharks and rays. For instance, the mean concentrations of Cu inMustelusmustelusfrom the Mediterranean Sea (Storelli et al, 2011), Chiloscylliumplagiosum from Southern waters of Hong Kong (Cornish et al, 2007) and Scyliorhinuscaniculus from the Northeast Atlantic (Celik&Oehlenschlager, 2004) werereported as being 0.71 mg/kg, 0.15 mg/kg and 0.51 mg/kg, respectively.But Cu has not been detected in tiger sharks (Galeocerdocuvier), from the coast of Ishigaki Island, (Endo, Hisamichi, Haraguchi, Kato &Ohta, 2008). Then Guerin et al(2011) reported that Cu concentrations in catsharks and rays as being 0.421 and 0.174mg/kg, respectively.…”
Section: Metal Concentrations In Thornback Rays and Spiny Dogfishmentioning
confidence: 99%
“…In this study, the Zn content of all the samples analyzed were found to be below this value. Likewise, Zn concentrations in various species of sharks (Celik & Oehlenschlager, 2004;Cornish et al, 2007;Endo et al, 2008;Storelli et al, 2011) and rays (Jones, Mercurio& Olivier,2000;Guerin et al, 2011) from :Differentletters in thesamerowshowstatisticaldifferences (P < 0.05). Olmedo et al (2013).…”
Section: Metal Concentrations In Thornback Rays and Spiny Dogfishmentioning
confidence: 99%
“…Fish are an important source of metals in human nutrition, and those from metal-contaminated sites present a potential risk to human health [27]. According to the mechanisms of absorption, regulation, storage, and excretion of metals, the various fi sh tissues present varying bioaccumulation rates [28].…”
Section: Effects Of Dps Extract On Heavy Metals Toxicity Of Fishmentioning
confidence: 99%